Multigenerational Modeling of Money Management - Christina M. Rosa; Loren D. Marks; Ashley B. LeBaron; E.Jeffrey Hill (Journal of Financial Therapy, 2018)
This study is about implicit financial socialization within families. It specifically examines how parental modeling facilitates the intergenerational transmission of healthy financial behaviors. This qualitative, multi-generational, multi-site study begins to answer the following research question: What financial behaviors are parents modeling for their children? The sample for this study (N=115) included 90 undergraduate students (ages 18-30) enrolled in family finance classes at three U.S. universities, 18 of their parents, and 7 of their grandparents. Using a team-based approach to qualitative data collection, analysis, and coding, four consensus themes related to parental financial modeling were distilled: (1) Working for a living (2) Managing money wisely (3) The importance of generosity and (4) Sacrificing for children. These ideas can be used by parents, family life educators, financial therapists, and others to help improve the quality of financial socialization within families.
Keywords: financial socialization; financial modeling; family finance; parenting; Millennials; emerging adults; qualitative; multigenerational